2017
DOI: 10.1007/s12020-017-1285-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between lifestyle and anthropometric parameters and thyroid nodule features

Abstract: Body fat accumulation and lack of exercise, used as surrogate markers of sedentary lifestyle, influence thyroid nodule size and could predict some ultrasonographic characteristics, like hypoechoicity and internal vascularity. Therefore, routine thyroid examination of obese patients and promotion of active lifestyle may be warranted to prevent thyroid nodule formation and possibly progression to malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 37 publications
6
33
0
Order By: Relevance
“…Although the connection between obesity and thyroid nodules is conflicting in the literature (Cappeli et al, 2012;Sousa et al, 2013), our study showed that the variables related to subcutaneous adiposity, cervical variables, were associated with a higher frequency of nodules. Moreover, a positive association between total body fat percentage and presence of thyroid nodules was verified in a cross-sectional study of 306 healthy individuals from northern Greece, which also agrees with our study findings (Panagiotou et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Although the connection between obesity and thyroid nodules is conflicting in the literature (Cappeli et al, 2012;Sousa et al, 2013), our study showed that the variables related to subcutaneous adiposity, cervical variables, were associated with a higher frequency of nodules. Moreover, a positive association between total body fat percentage and presence of thyroid nodules was verified in a cross-sectional study of 306 healthy individuals from northern Greece, which also agrees with our study findings (Panagiotou et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“… 5 , 20 , 21 The differences in the prevalence may be due to age, gender, race, culture, dietary patterns, and iodine supplements. 7 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…Some well-known factors involved in the formation and progression of TN, such as age, gender, iodine deficiency, and thyroid-stimulating hormone (TSH) [3]. More recently, the role of systemic inflammatory response caused by unhealthy lifestyle such as high calorie intake, sedentary behaviour, and chronic stress in the pathophysiology of TN has also attracted the interest of researchers [4][5][6].…”
Section: Introductionmentioning
confidence: 99%